Screening the Beats : media culture and the Beat sensibility - Sterritt, David (Southern Illinois University Press, 2004)
"Film critic David Sterritt's Screening the Beats: Media Culture and the Beat Sensibility showcases the social and aesthetic viewpoints of lynchpin Beat writers Jack Kerouac, William S. Burroughs, and Allen Ginsberg, juxtaposing their artistry with 1950s culture and achieving what Kerouac might have called a "bookmovie" riff. In clear prose, Sterritt captures the raw energy of the Beats and joins in their celebration of aesthetic freakishness. Tapping into the diversified spirit of the Beat Generation and its nuanced relationship with postwar American culture, Sterritt considers how the Beats variously foreground, challenge, and illuminate major issues in Hollywood and avant-garde film, critical and cultural theory, and music in the mass-media age."--Jacket.